Environmental monitoring and management proposals for the Fildes Region, King George Island, Antarctica - Braun, Christina; Mustafa, Osama; Nordt, Anja; Pfeiffer, Simone; Peter, Hans-Ulrich (Polar Research, 2012)
The Antarctic terrestrial environment is under increasing pressure from human activities. The Fildes Region is characterized by high biodiversity, but is also a major logistic centre for the northern Antarctic Peninsula. Different interests, from scientific research, nature conservation, protection of geological and historical values, station operations, transport logistics and tourism, regularly overlap in space and time. This has led to increasing conflict among the multiple uses of the region and breaches of the legal requirements for environmental protection that apply in the area. The aim of this study was to assess the impacts of human activities in the Fildes Region by monitoring the distribution of bird and seal breeding sites and recording human activities and their associated environmental impacts. Data from an initial monitoring period 200306 were compared with data from 200810. We observed similar or increased levels of air, land and ship traffic, but fewer violations of overflight limits near Antarctic Specially Protected Area No. 150 Ardley Island. Open waste dumping and oil contamination are still major environmental impacts. Scientific and outdoor leisure activities undertaken by station personnel are more frequent than tourist activities and are likely to have a commensurate level of environmental impact. Despite the initial success of some existing management measures, it is essential that scientific and environmental values continue to be safeguarded, otherwise environmental impacts will increase and the habitat will be further degraded. We argue that the Fildes Region should be considered for designation as an Antarctic Specially Managed Area, a measure that has proven effective for environmental management of vulnerable areas of the Antarctic.
Keywords: Antarktis; biodiversitet; miljøvern

Global Marine Flyways Identified for Long-Distance Migrating Seabirds From Tracking Data - Morten, Joanne M.; Carneiro, Ana P. B.; Beal, Martin; Bonnet-Lebrun, Anne-Sophie; Dias, Maria P.; Rouyer, Marie-Morgane; Harrison, Autumn-Lynn; González-Solís, Jacob; Jones, Victoria R.; Garcia Alonso, Virginia A.; Antolos, Michelle; Arata, Javier A.; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad-scale oceanic migration routes (?marine flyways?) used by multiple pelagic, long-distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989?2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long-distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad-scale flyways followed by most pelagic migratory seabirds tracked to-date at an ocean-basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure-of-eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind-driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean-basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.
Publisher: John Wiley & Sons, Ltd Article number: e70004
Keywords: Sørishavet; biogeografi; biologging; sjøfugler; økologi